2009
DOI: 10.1186/1471-2296-10-59
|View full text |Cite
|
Sign up to set email alerts
|

Attitudes, norms and controls influencing lifestyle risk factor management in general practice

Abstract: Background: With increasing rates of chronic disease associated with lifestyle behavioural risk factors, there is urgent need for intervention strategies in primary health care. Currently there is a gap in the knowledge of factors that influence the delivery of preventive strategies by General Practitioners (GPs) around interventions for smoking, nutrition, alcohol consumption and physical activity (SNAP). This qualitative study explores the delivery of lifestyle behavioural risk factor screening and managemen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

19
187
0
3

Year Published

2010
2010
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 157 publications
(213 citation statements)
references
References 6 publications
19
187
0
3
Order By: Relevance
“…The 3-session group-based intervention tested in schools was associated with a reduction in cigarettes smoked per day among adolescent participants, although no significant effect on smoking abstinence was observed. These findings are consistent with those reported in other studies, which have shown that school-based interventions, if well designed, can be effective in reducing short-term abstinence and reducing daily cigarette consumption; however the effectiveness on long-term smoking abstinence remains unclear 7,8,15 . While the primary study outcome was complete abstinence from smoking, it should be noted that reducing tobacco consumption may increase the chance of quitting in the future.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…The 3-session group-based intervention tested in schools was associated with a reduction in cigarettes smoked per day among adolescent participants, although no significant effect on smoking abstinence was observed. These findings are consistent with those reported in other studies, which have shown that school-based interventions, if well designed, can be effective in reducing short-term abstinence and reducing daily cigarette consumption; however the effectiveness on long-term smoking abstinence remains unclear 7,8,15 . While the primary study outcome was complete abstinence from smoking, it should be noted that reducing tobacco consumption may increase the chance of quitting in the future.…”
Section: Discussionsupporting
confidence: 91%
“…Practitioners' perception of self-efficacy in delivering smoking cessation interventions was assessed using a 6-item questionnaire allowing responses on a 10-point rating scale; with 1 -indicating lack of confidence and 10 -extreme confidence. This has been adapted from previously published instruments [13][14][15][16] . Study 2 examined the effectiveness of a pilot smoking cessation intervention that drew on the TOBg Guidelines and was delivered in a sample of highschools in Greece.…”
Section: Outcome Measures and Instruments Of Studymentioning
confidence: 99%
“…The views expressed by clinicians that CVD prevention is compromised by illness-based funding models, time pressures and a health workforce not well prepared for CVD preventive activities, are consistent with other exploratory studies in Australian primary care (Harris et al 2005;Ampt et al 2009;Passey et al 2010). Chronic disease management is incentivised in Australian primary care but this principle does not extend to CVD preventive activities, even though incentives have been shown to influence provider behaviour ).…”
Section: Current Primary Health Care System and Workforce In Rural Ausupporting
confidence: 66%
“…A variety of barriers to implementation exist at the patient, practitioner, service and system levels. 5 For example, GPs may have insufficient time with each patient to offer planned, effective preventive care. Barriers to referral for additional assistance include availability, appropriateness to the individual and cost to the patient, as well as lack of feedback to the GP.…”
Section: Barriers To Preventive Carementioning
confidence: 99%